(untitled) (Ágora Journal, 2025)
This paper aims to analyze the possibilities of identifying a legal experience among Japanese immigrants and Japanese Brazilians, using the theoretical framework of global legal history and the historiographical category of legal pluralism. To do so, it first situates the context of the Japanese immigration wave to Brazil in the early 20th century, then moves on to examine the specific characteristics of Japanese immigration and the cultural integration of this population, in order to inquire whether it is possible to identify flows of normative knowledge. In this regard, the study focuses on the experience of the Novo Oriente Colony as its main object, drawing on existing historiography as well as sources such as reports from the National Security Council and records from the DEOPS/SP. The hypothesis of this research is that it is indeed possible to identify flows of normative knowledge and expressions of legal pluralism in the history of Japanese immigration in Brazil, which would reveal an effective legal experience among the immigrants. The conclusion confirms this hypothesis, identifying the translation of normative knowledge by the immigrants and an expression of legal pluralism in the history of the Novo Oriente Colony.